A lethal disease of the European bison – posthitis is conditionally determined by its genomics - Sazia Kunvar; Sylwia Czarnomska; Cino Pertoldi; Astrid V. Stronen; Iwona Ruczyńska; Małgorzata Tokarska (Scientific Reports)
Abstract Posthitis is an incurable lethal disease of males of the European bison (Bison bonasus), regarded to be one of the major threats to the survival of the iconic species. Multiple attempts have been undertaken over the last 30 years to identify a source of infection and a primary pathogen. Studies indicated the disease could have a genetic background after tools developed for cattle (Bos taurus) revealed genomic regions that could be associated with its occurrence. In this study, we applied deep coverage targeted sequencing to 74 regions on 10 of the bison’s chromosomes (1, 9, 12, 13, 15, 23, 25, 26, 29, and X) in search for species-specific single nucleotide polymorphism (SNP) markers that could help to explain the mechanism of the disease and be used to test for posthitis susceptibility. The association results were ranked based on p-values lower than 0.005 and odds ratios (OR) higher than 1. We obtained 30 SNP markers that met these requirements, all located on chromosome 25. However, none of the SNPs found in the study was significantly associated with posthitis occurrence after Bonferroni correction. The conditional nature of posthitis and ‘false negative’ sampling represent major difficulties in investigating this disease, and we recommend a complex genomic and environmental factors association assay that could eventually explain the puzzling etiology of posthitis and help mitigate this threat to the European bison.